PENGARUH SISTEM PENGGAJIAN DAN UPAH LEMBUR TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN PT. ANPING SEAFOOD INDONESIA - Marshanda Twain Mukuan; Prisca Patricia Liem; Gebriany Pirade Wenur (Tangkoko: Jurnal Manajemen dan Akuntansi, 2026)
This study aims to examine the effect of the Payroll System and Overtime Pay on Employee Performance at PT. Anping Seafood Indonesia. The research employed a quantitative approach with an associative research design. The sample consisted of 72 operational employees selected from a population of 103 employees. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that the Payroll System has a positive and significant effect on Employee Performance, while Overtime Pay does not have a significant partial effect on Employee Performance. However, simultaneously, the Payroll System and Overtime Pay significantly affect Employee Performance. The coefficient of determination (R²) of 74.7% indicates that variations in Employee Performance can be explained by these two variables, while the remaining 25.3% is influenced by other factors outside the research model. These findings suggest that the Payroll System is the most dominant factor affecting Employee Performance at PT. Anping Seafood Indonesia.